Analysis of Perceived Need, Price Perception, and E-Marketing on Treatment Intention Affecting the Selection Decision for Dola Dental Clinic - Wattimena, Morasela (Dinasti Publisher, 2025)
This study aims is to find out, analyze, and test the effect of needs, price perceptions, and e-marketing on the decision to choose dental health services through interest in treatment. The study used a descriptive method with a qualitative approach, data analysis techniques in this study used structural equation models (SEM) with the help of the Lisrel program. The primary data of the study was obtained through a survey of 130 patients who used dental health services at the Dola Dental Clinic. The results of the study show that all hypothesis are accept with significant number. The study shows strong relation between the effect of needs, price perceptions, and e-marketing on the decision to choose dental health services through interest in treatment.